Neonatal Clonazepam Administration Induces Long-Lasting Changes in Glutamate Receptors - Kubová, Hana; Bendová, Zdenka; Moravcová, Simona; Pačesová, Dominika; Rocha, Luisa Lilia; Mareš, Pavel (Frontiers in Molecular Neuroscience, 2018)
Gama-aminobutyric acid (GABA) pathways play an important role in neuronal circuitry formation during early postnatal development. Our previous studies showed an increased risk for adverse neurodevelopmental consequences in animals exposed to benzodiazepines, which enhance GABA inhibition via GABAA receptors. We reported that administration of the benzodiazepine clonazepam (CZP) during postnatal days 7-11 resulted in permanent behavioral alterations. However, the mechanisms underlying these changes are not known. We hypothesize that early CZP exposure modifies the development of glutamatergic receptors and their composition because of the tight developmental link between GABAergic functions and the maturation of glutamatergic signaling. These changes may alter excitatory synapses and the neuronal connectivity and functioning of the neural network. We used quantitative real-time PCR and quantitative auroradiography to examine changes in NMDA and AMPA receptor composition. CZP (1 mg/kg/day) was administered for five consecutive days starting on P7. Brains were collected 48 h, 1 week and 60 days after treatment cessation, and mRNA subunit expression was assessed in the hippocampus and sensorimotor cortex. Patterns of CZP-induced alterations in subunit mRNA expression were dependent on the brain structure, interval after CZP cessation and receptor subunit type. In the hippocampus, up-regulation of GluN1and GluN3 and GluR1 and GluR2 subunit mRNA was found at the 48-h interval, and GluN1, GluN2A and GluR1 mRNA expression levels were higher 1 week after CZP cessation compared to controls. The expression of all measured subunit mRNAs was down-regulated by 5-13% at the 2-month interval, except GluN2B, which was not changed. CZP exposure increased GluN3 and GluR2 subunit mRNA expression levels in the sensorimotor cortex 48 h after treatment cessation. GluN2A mRNA was significantly up-regulated two months later, but the expression of other subunits was not different from the controls. NMDA receptor binding increased 1 week after the end of exposure in most hippocampal areas and most cortical areas, including the sensorimotor cortex, at the 48-h interval. Chronic CZP exposure decreased NMDA receptor binding in most evaluated hippocampal and cortical areas. Overall, early CZP exposure likely results in long-term glutamatergic receptor modulation that may affect synaptic development and function and potentially causes behavioral impairment.